Equality and global justice - Ip, K (2012)
This dissertation aims to defend an egalitarian conception of global distributive justice. Many hold that the scope of egalitarian justice should be defined by membership of a single political community but my dissertation will challenge this view. I begin by considering three distinctive arguments against the ideal of global equality. They maintain that egalitarian obligations of justice apply only to those people who are subject to the same sovereign authority which coerces them to abide by its rules; or to those who contribute to the preservation of each other’s autonomy through collectively sustaining a state; or to those who belong to the same nation. The first three chapters deal with these arguments respectively. Central to these arguments is the assumption that the domestic and the global contexts are different in some morally relevant way so egalitarian principles of justice apply to the former but not the latter. After rebutting these anti-egalitarian arguments I turn to the more constructive task of developing a form of global egalitarianism that is grounded in the value of equality as a normative ideal of how human relations should be conducted. I argue in Chapter 4 that relational equality—that is, standing in relations of equality to one another (rather than relations characterized by domination or exploitation)—is a demand of justice in the global context. This ideal of relational equality has distributive implications. In Chapter 5 I try to spell out these implications by defending a set of principles of global distributive justice that would follow from our commitment to global relational equality. In the sixth and final chapter, I discuss what responsibilities we have in relation to global injustice, how to distribute the burdens associated with these responsibilities, and whether they are excessively demanding on complying agents.